Table of Content - -, (Journal of Educational and Psychological Sciences, 2023)
Table of Content1. The reality of digital transformation governance and the obstacles to its application at Princess Noura bint Abdel Rahman University from the point of view of academic leaders in the faculties of education, administration and businessMrs. Ohoud Talal Alhazmi2. Applications Artificial intelligence and their role in developing Smart Content from the point of view of faculty membersMrs. Najwa Mohammed Al-Shammari3. The Impact of Distance Education on Achieving the Effectiveness of the Educational Process During the Corona Pandemic, A Case Study on Princess Nourah University in RiyadhMrs. Sarah Homoud Al-Kahtani4. Challenges of Scientific Research in Palestinian Universities and Avenues for its Enhancement: Perspectives of Ph.D. Students in West Bank UniversitiesDr. Osama Issam Matar, Dr. Reem Mashhour Jawabreh , Mrs. Haya Yaser Radwan ,Mr. Thaher Mohamed Gharabeh , Mrs. Sherin Wael Kaleef, Dr. Mohammad shareef ayyash , Mr. Diya Mohammed Abu shomer , Mr. Abedelrahman Aqel Alhajhamad , Mrs. Aseel Adly Halabi , Dr. Ashraf Mohammed Abualrob 5. The Relationship between Adjustment Disorder and Emotional Regulation among Sample of adults in TabukMrs. Wejdan Abdulrhman Algarni, Dr. Ahmed Ali Alhomidi6. Students’ Perceptions of Gamification in Higher EducationDr. Alaa Khaled Nyazi
Keywords: Journal of Educational and Psychological Sciences